Dampak Industri Game Lokal Terhadap Perekonomian Kreatif Dan Penyerapan Tenaga Kerja Muda - Zuhruf Nahdah Roosyidah; Siswadi (Lembaga Teewan Journal Solutions, 2026)
The local game industry is one of the fastest-growing sectors of Indonesia’s creative economy, supported by rapid digital transformation and increasing internet penetration. This study aims to analyze the impact of the local game industry on the creative economy and its contribution to youth employment using a Systematic Literature Review (SLR) approach. The research process involved problem identification, literature searching, article selection based on inclusion and exclusion criteria, data extraction, and synthesis of findings from scientific publications over the last ten years. The review shows that the local game industry significantly contributes to the creative economy by generating high-value digital products, encouraging technological innovation, and strengthening the digital economic ecosystem. It also creates diverse employment opportunities for young people, including careers as programmers, game designers, animators, digital illustrators, and content creators. However, the industry continues to face challenges such as skill gaps, limited access to funding, and strong competition from foreign game products in the domestic market. To address these issues, greater collaboration among government agencies, educational institutions, and industry stakeholders is essential to improve workforce competencies, support innovation, and enhance the competitiveness of local game developers, thereby maximizing their contribution to Indonesia’s creative economy and youth employment.